2012: An elemental force: Uranium production in Africa, and what it means to be nuclear. (1st November 2020) - Hecht, Gabrielle
ABSTRACT: Uranium from Africa was, and remains, a major source of fuel for atomic weapons and power plants throughout the world. Uranium for the Hiroshima bomb, for example, came from the Belgian Congo. During any given year of the Cold War, between 20 percent and 50 percent of the Western world's uranium came from African places: Congo, Niger, South Africa, Gabon, Madagascar, and Namibia. Today, there is a renewed uranium boom throughout the continent. The author writes on the ambiguities of the nuclear state, and the state of being nuclear, and why the nuclear designation matters. She looks at two countries to uncover different dimensions of nuclearity: Niger, which has long struggled with France over the price of its uranium; and Gabon, where cancer and other illnesses related to four decades of uranium production remain invisible.